Preventing Iron-Deficiency Anemia in Children in Developing Countries — Why it is Necessary and How it Must be Approached - Dogra, Nupur (The Meducator, 2013)
Iron deficiency (ID) has been identified as the most common nutritional deficiency condition in the world, with a high prevalence in both developed and developing countries. ID and iron-deficiency anemia (IDA) affect the cognitive, socioemotional and motor development of children. Using evidence from 2002 onwards, a literature review of the impact of ID and IDA on child development and the interventions preventing them was conducted. Review of recent evidence presents 1) altered cognitive functions, 2) decreased socio-emotional development, and 3) impediment of motor skills development due to ID and IDA . In conclusion, the effects of ID and IDA on child development are significant and often irreversible. Viable and effective preventive programs, such as iron supplementation, diet diversification, food fortification and early and home interventions, are favoured over curative measures.